IMPLEMENTASI PEMBAYARAN GANTI RUGI KEUANGAN DAERAH OLEH PEGAWAI NEGERI BUKAN BENDAHARA DI PROVINSI RIAU TAHUN 2022 - Siti Nurhaliza; Evi Deliana; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In order to realize good governance in state administration, it is necessaryto implement professional, open and responsible state financial management inaccordance with the principles of state financial management. The embodiment ofstate financial management is outlined in the State Revenue and ExpenditureBudget (APBN) and Regional Revenue and Expenditure Budget (APBD). Mistakesin using the budget can result in State/Regional Losses. Based on interviews withthe Regional Financial and Asset Management Agency, there were several non-treasurer civil servants who caused regional losses. Settlement of regional lossescarried out is regulated in Domestic Government Regulation Number 133 of2018. The aim of this research is to find out the extent of implementation relatedto settlement of losses carried out by non-treasurer civil servants in RiauProvince, what factors hinder the settlement of compensation for losses carriedout and what efforts will be made regarding the settlement of compensation forexisting regional financial losses.This research is sociological legal research, namely looking at therelationship between law and society with the gap between the law as it should beand the law as it actually occurs. This research was conducted at the RegionalAsset Finance Agency of Riau Province and at the Riau Inspectorate. Datacollection techniques through interviews.From the results of the research that has been carried out, implementationhas not been carried out well, the factor causing it not to be carried out well isthat new regulations have just been issued that are more detailed in regulatinglosses incurred by non-treasurer civil servants in Riau Province.Keywords : Regional Losses, Non-Treasurer Civil Servants, Loss Settlement.